(3Mce GdJShjb HYehdI gQejI (B:s (3OQGSI abgjI bGfhfjI ebGQfI (B/s - (3bQfj, CMeO SejQs ((3YeGf(B: s (3OGQ GdfaGFS ddfTQ hGdJhRjY(B, s, 2012)
(3GdJYQja HGdJShjb GdgQej hHjGf CgejJg hMbjbJg(B- (3HjGf ePgH GdabgGA GdeYGUQjf ef gPg GdbVjI(B- (3ebGQfI Hjf ehba GdbhGfjf GdZQHjI hehba Gdabg GdESdGej ef gPg GdbVjIs
(3GdeQGLY U(B.171s
Keywords: (3COGQI GdeHjYGJs; (3GdEbJUGO GdESdGejs; (3GdJShjbs